2013
DOI: 10.5812/ircmj.11558
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Knowledge Among Iranian Adolescents: A National Survey

Abstract: Background:Hepatitis B is the most prevalent chronic infectious liver disease worldwide with serious sequelae. Prevention of the infection can be provided by universal vaccination and improvement in knowledge and behavior about disease transmission. Provision of any educational program requires inquiry about target group baseline knowledge.Objectives:The aim of this study was to assess Iranian adolescents’ knowledge about hepatitis B (HBV) and associated factors.Patients and Methods:We conducted a questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 17 publications
3
9
0
Order By: Relevance
“…Multivariate analysis highlighted an association between educational level and HB knowledge in this study. This result is in line with current literature [ 16 , 17 , 22 , 30 ] which reported that a higher level of qualification positively correlates with knowledge about HB. Since the prevalence of HB is higher in those in an economically and socially vulnerable situation [ 28 ], this finding underlines the necessity to reduce social inequalities in health [ 22 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Multivariate analysis highlighted an association between educational level and HB knowledge in this study. This result is in line with current literature [ 16 , 17 , 22 , 30 ] which reported that a higher level of qualification positively correlates with knowledge about HB. Since the prevalence of HB is higher in those in an economically and socially vulnerable situation [ 28 ], this finding underlines the necessity to reduce social inequalities in health [ 22 ].…”
Section: Discussionsupporting
confidence: 93%
“…Since the prevalence of HB is higher in those in an economically and socially vulnerable situation [ 28 ], this finding underlines the necessity to reduce social inequalities in health [ 22 ]. Other authors found age, female gender, marriage, social status and living in rural areas were associated with better knowledge [ 16 , 19 , 22 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lack of education regarding the method of transmission may have helped the spread of infection. Previously, it was shown that having knowledge about any disease, especially contagious, might help decreasing the spread of that disease (17). In a study conducted in Singapore, it was shown that 70% of the participants knew about the mode of transmission of HBV (18).…”
Section: Discussionmentioning
confidence: 99%
“…A high percentage of married youth had appropriate HBV knowledge (P<0.001), and this had a direct relationship with the spouse's education level (P=0.007). The rate of correct answers to the questions is shown in Table 1 (24). In the part of seriousness of the disease, the lowest level of knowledge was about the hepatitis B risk of cancer (38.1% correct answer).…”
Section: Resultsmentioning
confidence: 99%